Forecasting the Trends and Probable Impact of COVID-19 on Low and Middle Income Countries based on the publicly available data (The Lumbini Journal of Business and Economics, 2021)
The COVID-19 pandemic becomes a public-health threat globally exerting a devastating impact on patients, healthcare providers, systems, and financing. Both developed and developing countries are struggling to control the pandemic, though situation is alarming in Low-and-Middle-Income-Countries (LMICs). Lack of social-distancing, higher population, health-inequalities, adequate health infrastructure is placing tremendous challenge to control COVID-19. Present study was undertaken to forecast the trends in outbreak of COVID-19 in LMICs (40 countries) based on the publicly-available-case-data drawn from thehttps:// ourworldindata.org/coronavirus-source-data. An auto-regressive-integrated-moving-averages (ARIMA) model was used to predict the trends in total confirmed and death-cases caused by COVID19. Findings reveal the highest point-forecast of confirmed-case rate for Zambia (2.13%) and lower death rate (0.48%) in Morocco across LMICs. Keeping in view the limited healthcare resources in LMICs, accurate forecasting and detection, stronger disease-surveillance, and avoidance of acute-care for infected-cases is indispensable.